What does physicians' clinical expertise contribute to oncologic decision‐making? A qualitative interview study. Issue 1 (27th October 2017) - Salloch, Sabine; Otte, Ina; Reinacher‐Schick, Anke; Vollmann, Jochen
Abstract: Background: Physicians' clinical expertise forms an exclusive body of competences, which helps them to find the appropriate diagnostics and treatment for each individual patient. Empirical evidence, however, suggests that there is an inverse relationship between the number of years in practice and the quality of care provided by a physician. Knowledge and adherence to professional standards (such as clinical guidelines) are often used as indicators in previous research. Methods: Semistructured interviews and the Q method were used for an explorative study on oncologists' views on the interplay between their own clinical expertise, intuition, and the external evidence incorporated in clinical guidelines. The interviews were audio recorded, transcribed ad verbatim, and analysed using qualitative content analysis. Results: Data analysis shows the complex character of clinical expertise with respect to experience, professional development, and intuition. An irreplaceable role is attributed to personal and bodily experience during the providing of care for a patient. Professional experience becomes important, particularly in those situations that lie out of the focus of "guideline medicine." Intuition is regarded as having a strong emotional component and helps for deciding which therapeutic option the patient can deal with. Conclusions: Using measurable knowledge and adherence to standards as indicators does not account for the complexity of clinical expertise. Other factors, such as the importance of bodily experience and physicians' intuitive knowledge, must be considered, also with respect to the occurrence of treatment biases.